Landscaping tuberculosis multimorbidity: findings from a cross-sectional study in India - A. Chauhan; M. Parmar; J. D. Rajesham; S. Shukla; K. C. Sahoo; S. Chauhan; S. Chitiboyina; A. Sinha; G. Srigana; M. Gorla; Sanghamitra Pati (BMC, 2024)
Abstract Background Multimorbidity, the concurrent presence of two or more chronic conditions is an emerging public health challenge. Till date, most of the research have focused on the presence and interaction of selected co-morbidities in tuberculosis (TB). There exist a critical knowledge gap on the magnitude of multimorbidity among TB patients and its impact on health outcomes. Methods We undertook a cross-sectional study to assess the prevalence and patterns of multimorbidity among newly diagnosed TB patients in two states of India. A total of 323 patients were interviewed using a structured multimorbidity assessment questionnaire for primary care (MAQ-PC). MAQ-PC is already validated for Indian population and elicits 22 chronic conditions. We defined TB multimorbidity as the co-existence of TB with one or more chronic conditions and identified commonly occurring dyads (TB + single condition) and triads (TB + two conditions). Results More than half (52%) of TB patients reported multimorbidity. Among dyads, depression, diabetes mellitus (DM), acid peptic disease (APD), hypertension, chronic alcoholism, arthritis and chronic back ache (CBA) were the most common co-occurring conditions while 'DM + arthritis', 'depression + APD', 'depression + DM' were the most commonly occurring triads among TB patients. Factors such as increasing age, low levels of education, alcohol abusers, drug-resistant TB and having health insurance were significantly associated with multimorbidity among TB patients. Conclusions Our findings suggest high prevalence of multimorbidity among newly diagnosed TB patients in India. The presence of concordant and discordant conditions with TB may increase the health complexity, thus necessitating appropriate care protocols. Given, the current situation, wherein TB and non-communicable diseases (NCD) services are delivered through collaborative framework between programmes, there is a need for addressing multimorbidity at the healthcare delivery level.